Lymphatic Microsurgical Preventive Healing Approach for the Primary Prevention of Lymphedema: A 4-Year Follow-Up. Issue 2 (15th November 2022) - Levy, Adam S.; Murphy, Alexander I.; Ishtihar, Sherene; Peysakhovich, Anya; Taback, Bret; Grant, Robert T.; Ascherman, Jeffrey A.; Feldman, Sheldon; Rohde, Christine H.
Abstract : Background: Axillary lymph node dissection (ALND) remains the leading cause of lymphedema nationally, and there is still no cure for the disease. The lymphatic microsurgical preventive healing approach (LYMPHA) is a promising option for lymphedema prophylaxis in patients undergoing ALND, but long-term outcomes of the LYMPHA are not well established. Methods: The authors conducted a retrospective review of patients undergoing ALND at their center from November of 2012 to November of 2016 and assembled two cohorts, those who received the LYMPHA and those who did not (non-LYMPHA). Patient data were collected to evaluate lymphedema risk and long-term lymphedema incidence of each group. Results: Forty-five women were included in both our LYMPHA and non-LYMPHA cohorts. Mean body mass index (27.7 kg/m 2 versus 29.9 kg/m 2 ; P = 0.15) and radiation therapy rates (60.0% versus 68.9%; P = 0.51) did not differ between groups. Non-LYMPHA patients underwent complete mastectomy more frequently than LYMPHA patients (97.8% versus 77.8%; P = 0.007), but had a similar number of nodes removed during ALND (14.4 versus 15.8; P = 0.32). Median follow-up time was greater than 4 years for both LYMPHA and non-LYMPHA groups (57.0 months versus 63.0 months; P = 0.07). Overall, lymphedema incidence was 31.1% in the LYMPHA group and 33.3% in the non-LYMPHA group ( P > 0.99). No significant differences in lymphedema incidences were observed between the LYMPHA and non-LYMPHA groups for patients with obesity, patients who received radiation therapy, or patients with obesity who also received radiation therapy ( P > 0.05 for all subgroups). Conclusions: The LYMPHA may not prevent lymphedema long-term in patients who undergo ALND. More long-term studies are needed to determine the true potential of the procedure. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.